Defending the earth - Bookchin, Murray (Black Rose Books, 1991)
"Defending the Earth brings together two of the main protagonists in the heated deep vs. social ecology debate: eco-philosopher Murray Bookchin and Earth First! founder Dave Foreman. Bookchin and Foreman seek common ground and cooperatively explore their differing, though often overlapping, perspectives on a wide variety of issues."